Diversity of Endemic Ectomycorrhizae of Humid Forests of South Cameroon - Nérée, Onguene Awana; Bechem, Eneke Tambe; Ambroise, Yene Mbarga; Marthiale, Tsamo Judith; Victor, Ngouo Léopold (Journal of Environmental Science and Engineering Technology, 2022)
The ecologically important below-ground ectomycorrhizal (ECM) biodiversity of tropical humid forests remain poorly known. Most ECM inventories have been based upon description and identification of fruitbodies with few work on ECM root tips of tropical tree species. Morpho-anatomical descriptions of root tips of 24 ECM Fabaceae/Detarioideae, Uapaca tree species, and Gnetum lianas were conducted in humid forest of South Cameroon. ECM forest clumps were the only resort sites for the more than 30 endemic ECM morphotypes, with apparently no host specificity. Distinguished by four colors – white, yellow, brown, and dark brown – and five textures – smooth, cottony, woolly, spiny and verrucose –, they differed from to the golden yellow coralloïdal Gnetum liana ECM with plectenchymatous mantle. Tree ECM were of monopodial-pinnate or -pyramidal types with external felt prosenchyma mantles shielded with abundant rhizomorphs, emanating hyphae and variously shaped cystida with clamp connections. These ECM fungal attributes may confer ECM associations with strong competitive abilities to strive at best on prevailing nutrient-poor acid soils and harsh conditions, thus better explaining tropical monodominance. Yet, much research is still needed to determine the role of below-ground ECM biodiversity on structure and functioning of tropical humid forests of the Congo basin.